Is Diversified Crop Rotation an Effective Non-Chemical Strategy for Protecting Triticale Yield and Weed Diversity? - Jastrzębska, Magdalena; Kostrzewska, Marta K.; Marks, Marek (Agronomy (Basel), 2023)
Diversified crop rotation (DCR) has re-gained attention worldwide as a non-chemical practice for increasing the sustainability of cereal production systems. This study focused on comparing the effects of two weed management strategies, DCR (the six-field system: potato–oat–fiber flax–winter rye–faba bean–winter triticale) without the application of a herbicide (DCR strategy) and with the application of a herbicide (DCR + H strategy) on the yield of winter triticale and on the biomass and species, taxonomic, and functional diversities of weed communities. In addition, the responses of two triticale cultivars, Trapero and Borowik, to the weed management strategies were evaluated. Data from five growing seasons (2017–2021) of a long-term experiment (Bałcyny, northeastern Poland) are presented. The DCR strategy proved less effective in protecting the triticale yield than DCR + H but provided greater weed species, taxonomic and functional diversities. Borowik had a higher yield and responded to herbicide abandonment with a lower yield loss. When the DCR strategy was used, Borowik was more competitive against weeds than Trapero without reducing weed diversity. The triticale yield correlated negatively with weed biomass and diversity, and weed diversity and weed biomass were positively correlated. The findings show that winter triticale can be grown in DCR without the application of a herbicide if a high-yield, competitive cultivar such as Borowik is used. Growing such a cultivar under DCR conditions without the application of a herbicide promotes weed diversity; however, in years with less favorable weather conditions, it may be necessary to accept a moderately lower yield compared to the yield provided with herbicide protection. The relationship between weed diversity and weather conditions is a subject for further research.